2013
DOI: 10.1080/03601234.2013.824300
|View full text |Cite
|
Sign up to set email alerts
|

Charcoal burning as a source of polyaromatic hydrocarbons in waterpipe smoking

Abstract: Polyaromatic hydrocarbons (PAH) content from seven commercial waterpipe charcoals were determined during the smoking process to estimate how much PAHs would not be trapped by the water trap and could reach the lungs of the smokers. Naphthalene, 2-methylnaphthalene, acenaphthylene, acenaphthene, phenanthrene and fluoranthene were the most abundant PAH compounds produced during smoking. Naphthalene was the highest in all of the smoke contents and levels of 5 to 405 μg/15 minutes could be inhaled by the smoker. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…The IARC reported that charcoal emissions are carcinogenic to humans, and benzene is one of its chemical constituents (72). Three studies have reported that charcoal used for hookah tobacco smoking contributed to quantities of CO and PAHs in mainstream hookah smoke; however, these studies did not quantify benzene in hookah charcoal emission (55,70,71).…”
Section: Percent Of Non-smokers Time Spent In Minutesmentioning
confidence: 99%
See 1 more Smart Citation
“…The IARC reported that charcoal emissions are carcinogenic to humans, and benzene is one of its chemical constituents (72). Three studies have reported that charcoal used for hookah tobacco smoking contributed to quantities of CO and PAHs in mainstream hookah smoke; however, these studies did not quantify benzene in hookah charcoal emission (55,70,71).…”
Section: Percent Of Non-smokers Time Spent In Minutesmentioning
confidence: 99%
“…Hookah tobacco is generally moist and does not burn in a self-sustaining manner, as with cigarettes (55,70,71). Therefore, burning charcoal is placed on top of the tobacco covered with perforated aluminum foil at the start of a use session, and is replaced one or more times during the smoking session (55,71).…”
Section: Percent Of Non-smokers Time Spent In Minutesmentioning
confidence: 99%
“…These toxicants include carbon monoxide (CO; [64,70,71]), polycyclic aromatic hydrocarbons (PAHs) [70,7274], volatile aldehydes [7577], and nicotine [64,71]. Exposure to these toxicants is associated with a variety of adverse health consequences including cardiovascular disease, cancer, and pulmonary disease, and nicotine/tobacco dependence.…”
Section: Toxicants In Waterpipe Tobacco Smokementioning
confidence: 99%
“…As with any tobacco smoking, waterpipe smoking exposes users to clinically harmful levels of tobacco-specific nitrosamines,[ 3 5 ] polycyclic aromatic hydrocarbons and other common toxicants found in tobacco. [ 6 8 ] Emerging evidence also suggests that users are at increased risk of cardiovascular diseases,[ 9 , 10 ] lung cancer,[ 11 ] and other respiratory conditions[ 12 , 13 ] relative to non-users.…”
Section: Introductionmentioning
confidence: 99%